DISTRIBUTION OF ASSASSIN BUGS (HETEROPTERA: REDUVIIDAE) STUDIED UNDER THE CONDITIONS OF UZBEKISTAN ACROSS DIFFERENT LANDSCAPES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of a comparative analysis of the biodiversity, ecological characteristics, and distribution of assassin bugs belonging to the family Reduviidae studied in Uzbekistan, based on literature sources. An analysis of scientific literature from various regions of the republic for the period 1916–2024, as well as field studies conducted in 2024–2025 in Kashkadarya and Surkhandarya provinces, revealed that representatives of Reduviidae possess a wide ecological range in the southern regions. During the study, 4 subfamilies, 11 genera, and 17 species of this family were recorded in mountain, foothill, desert, and agrobiosenosis landscapes. Literature analysis also showed that comprehensive studies on the fauna and ecology of Reduviidae in Southern Uzbekistan remain insufficient. As a result of this study, an updated checklist of assassin bug species recorded in the territory of Uzbekistan was compiled.